2015
DOI: 10.14814/phy2.12335
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating angiogenesis mitigates the unloading-induced reduction in osteogenesis in early-stage bone repair in rats

Abstract: Accelerating fracture healing during bed rest allows early mobilization and avoids prolonged fracture healing times. We tested the hypothesis that stimulating angiogenesis with deferoxamine (DFO) mitigates the unloading-induced reduction in early-stage bone repair. Rats aged 12 weeks were subjected to cortical drilling on their tibial diaphysis under anesthesia and treated with hindlimb unloading (HU), HU and DFO administration (DFOHU), or weight bearing (WB) for 5 or 10 days (HU5/10, DFOHU5/10, WB5/10; n = 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
(153 reference statements)
3
11
0
Order By: Relevance
“…Fracture callus and osteophyte development have both been shown to be sensitive to local biomechanics after injury . Previous studies have observed decreased osteophyte formation after unloading in a guinea pig model of chemically induced OA, and decreased fracture callus growth in a rat tibial fracture model . Our results agree with these studies, and suggest that loading from normal ambulation influences both osteophyte and fracture callus formation.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Fracture callus and osteophyte development have both been shown to be sensitive to local biomechanics after injury . Previous studies have observed decreased osteophyte formation after unloading in a guinea pig model of chemically induced OA, and decreased fracture callus growth in a rat tibial fracture model . Our results agree with these studies, and suggest that loading from normal ambulation influences both osteophyte and fracture callus formation.…”
Section: Discussionsupporting
confidence: 91%
“…9,14,39,[41][42][43][44] Previous studies have observed decreased osteophyte formation after unloading in a guinea pig model of chemically induced OA, and decreased fracture callus growth in a rat tibial fracture model. 6,7,24 Our results agree with these studies, and suggest that loading from normal ambulation influences both osteophyte and fracture callus formation. Tail suspension has been shown to decrease blood perfusion to hindlimbs, and angiogenic factors have been shown to combat the HLU-induced reduction in osteogenesis which may indirectly impact inflammation in hindlimbs, consequently affecting fracture callus and osteophyte formation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations